PERAMPANEL TREATMENT FOR GENERALISED TONIC-CLONIC SEIZURES. Issue 12 (15th November 2016) - O'Brien, Terence; Patten, Anna; Bibbiani, Francesco; Yang, Haichen; Williams, Betsy; Laurenza, Antonio
Abstract : Purpose: A post hoc analysis evaluated the efficacy and tolerability of perampanel across four Phase III studies in patients with secondarily generalised (SG) or primary generalised tonic-clonic (PGTC) seizures. Method: All studies involved patients aged ≥12 years. Studies 304 (n=388) and 305 (n=386) evaluated perampanel 8 or 12 mg/day or placebo. Study 306 (n=706) evaluated perampanel 2, 4, or 8 mg/day or placebo. These studies had a 19-week double-blind phase (6-week titration; 13-week maintenance). Study 332 (n=164) evaluated perampanel up to 8 mg/day or placebo (17-week double-blind phase; 4-week titration, 13-week maintenance). Full Analysis Set (FAS) included patients who had SG or PGTC seizures and received perampanel 8 mg/day. Results: FAS included 492 patients (mean age 31.7 years). Compared with placebo, perampanel conferred a greater median percent reduction in PGTC/SG seizure frequency per 28 days (−24.6% vs. −65.5%; p<0.0001), greater 50% responder rate (37.8% vs. 61.8%; p<0.0001) and higher rate of seizure freedom from PGTC/SG (12.6% vs. 26.9%). Compared with placebo, most common adverse events with perampanel were dizziness (5.9% vs. 28.6%), somnolence (5.9% vs. 13.4%), and headache (10.6% vs. 12.2%). Conclusion: Perampanel reduced generalised tonic-clonic seizure frequency, whether primary or SG, and was well tolerated. Funded by Eisai Inc.